“Woman” in the European Human Rights System: How is the Reproductive Rights Jurisprudence of the European Court of Human Rights Constructing Narratives of Women’s Citizenship? - Oja, Liiri; Yaminc, Alicia Ely (Columbia Journal of Gender and Law, 2016)
Reproductive rights are constructed through a gender-conscious reading of already recognized human rights. We argue that despite the increasingly strong recognition of reproductive rights in international human rights law by the treaty-monitoring bodies and international tribunals, the jurisprudence of the European Court of Human Rights (“ECtHR” or “the Court”) reflects a limited understanding of women’s experiences, does not adequately challenge gender stereotypes, and often ignores reproductive rights dimensions in the standards it is setting, as well as the narratives it is creating. Our analysis of the Court’s jurisprudence on abortion, home birth, non-consensual gynecological examinations, forced sterilizations, and assisted reproduction reveals that a woman’s reproductive capacity continues to be her defining feature. Motherhood is seen as a woman’s default life plan, her decisions regarding her body, health, and ultimately life, are perpetually under scrutiny and the contours of her agency subject to medical professionals’ views, the legislators and the general public.